ANALISIS WACANA KRITIS THEO VAN LEEUWEN TERHADAP PEMBERITAAN ANIES DI TOLAK ISI SEMINAR DI UGM - Fahmi Ismail Marzuqi; Agus Hamdani (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This research aims to examine the strategies of inclusion and exclusion used by Republika.com in relation to the news coverage titled "Beredar Pesan Singkat Anies Ditolak Datang Isi Seminar di UGM, Pihak Rektorat Membantah" using Theo Van Leeuwen's critical discourse analysis. The findings of this research will be utilized to suggest teaching resources. This study is qualitative and adopts a descriptive approach. The news coverage "Beredar Pesan Singkat Anies Ditolak Datang Isi Seminar di UGM, Pihak Rektorat Membantah" is the object of the research, with Republika.com as the focus of the study. In this investigation, it was discovered that Republika.com's reporting employs tactics of exclusion and inclusion. The results of Theo Van Leeuwen's critical discourse analysis can contribute to the knowledge of the public and readers. The findings of this research can be applied to theory development, aiming to understand the structure and linguistic norms of news text, both in oral and written forms. Keywords: Theo Van Leeuwen's Discourse Analysis, News, Exclusion, Inclusion